2017
DOI: 10.1038/cddis.2017.233
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB1 is a key regulator of acute but not chronic renal injury

Abstract: The NF-κB family of transcription factors is important for many cellular functions, in particular initiation and propagation of inflammatory and immune responses. However, recent data has suggested that different subunits of the NF-κB family can suppress the inflammatory response. NF-κB1, from the locus nfκb1, can inhibit transcription, acting as a brake to the recognised pro-inflammatory activity of other NF-κB subunits. We tested the function of NF-κB1 in an acute (nephrotoxic serum (NTS) nephritis) and a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Moreover, it is well established that p105 inhibits TPL2 kinase activity, reducing phosphorylation of ERK1/2 11 , and we demonstrate increased early phosphorylation of ERK1/2 at D3 in NFKB1 KO , relative to NFKB1 WT . In contrast, Fearn et al ., demonstrated that NFKB1 KO prevented ERK1/2 phosphorylation in bone marrow derived macrophages 23 , further exhibiting the cell type-specific effects of NFKB1 KO . In the present study, we found overall increases in canonical NF-κB and early ERK1/2 activation of cells involved in tendon healing, which we hypothesize to be due to the loss of repressive p50 homodimers and uninhibited TPL2 kinase.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, it is well established that p105 inhibits TPL2 kinase activity, reducing phosphorylation of ERK1/2 11 , and we demonstrate increased early phosphorylation of ERK1/2 at D3 in NFKB1 KO , relative to NFKB1 WT . In contrast, Fearn et al ., demonstrated that NFKB1 KO prevented ERK1/2 phosphorylation in bone marrow derived macrophages 23 , further exhibiting the cell type-specific effects of NFKB1 KO . In the present study, we found overall increases in canonical NF-κB and early ERK1/2 activation of cells involved in tendon healing, which we hypothesize to be due to the loss of repressive p50 homodimers and uninhibited TPL2 kinase.…”
Section: Discussionmentioning
confidence: 75%
“…52 The NF-κBdepleted mice showed increased glomerular injury, proteinuria, and inflammatory cytokine production during acute, but not chronic, renal injury. 53 Several inflammatory cytokines and chemokines such as TNF-α, IL-1, IL-6, IL-18, CCL2, and CCL5 have been found to be upregulated in kidney tissues and are associated with several renal effects, including enhanced vascular endothelial permeability, increased mesangial cell proliferation, affect extracellular matrix synthesis, and increased albuminuria. 6,[54][55][56][57][58] Studies have also suggested the implication of TNF-α in inducing the cellular apoptosis and necrosis pathways, the destabilization of the intraglomerular hemodynamics affecting the glomerular filtration rate, and the induction of NADPHmediated cellular oxidative stress leading to the production of ROS that eventually causes renal injury in diabetic human and mice.…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…The NF-κB transcription factors family found to have vital important in many functions inside cells, like initiation and propagation of inflammatory and immune responses (Fearn et al, 2017). Previous studies found that NF-κB has important role in the pathogenesis of renal inflammation caused by infection, injury, or autoimmune factors (Zhang andSun, 2015, Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%